Logica per un mondo in movimento. Ernst Bloch e il nichilismo - Vaccaro, Giovanbattista (Bollettino Filosofico, 2015)
The essay aims to explain where does Ernst Bloch stand on European nihilism of 20th century, regarding the crisis of logic in front of the rising idea of a moving world. In its last work, Experimentum mundi, Bloch highlights the centrality of the future in the dynamic structure of being, introducing a new ontology, based on the idea of the «Not-Yet Being».